Analisis Komparatif berdasarkan Faktor Demografi terhadap Kepuasan Kerja dan Turnover Intention pada Karyawan CV. Semoga Jaya di Samarinda - Eko Adi Kurniawan; Tetra Hidayati; Robiansyah Robiansyah (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This Research aim to analyze any factors that significantly affect the high and low turnover intention among employees. The number of samples taken in this study were 80 respondents permanent employees CV. Semoga Jaya Samarinda. This study sample was divided into several categories: gender, marital status, education, employment period.  The study concluded the level of employee satisfaction CV. Semoga Jaya Samarinda based on sex, marital status, level of education and long work is equal/no difference, because every employee is in the organization and management of a structured, co-workers harmonious working conditions conducive, moreover, supported by an adequate salary, and supervision that result is to give an opportunity to develop forward for all employees. The rate of employee turnover intention on the CV. Hopefully Jaya Samarinda between male employee/female, who have not and are married, low education and high education, as well as a new work or who have long worked is equal / no difference. The desire to get out of work, it will not happen if the job satisfaction of employees met with good.  Keywords: Job Satisfaction, Turnover Rates, Employee